Broadband terahertz metamaterial absorber with two interlaced fishnet layers - Siyu Tan (AIP Advances, 2018)
The realization of broadband absorption in the terahertz regime is of significant interest in high-sensitive signal detection and modulation. Previously, multi-layer metamaterials have been proposed and demonstrated to expand the absorption bandwidth by clustering multiple closely-positioned structures with different absorption peaks. Here, we proposed an alternative design for broadband metamaterial absorption by incorporating two interlaced fishnet layers, and achieved a broadband absorber with a full-width at half-maximum of about 0.99 THz. We also investigated the impact of the relative position of the two fishnet layers in the form of frequency tuning and expanding the absorption band.